Supramolecular Systems Containing B–N Frustrated Lewis Pairs of Tris(pentafluorophenyl)borane and Triphenylamine Derivatives - Chidchob, P.; Jansen, S. A. H.; Meskers, S. C. J.; Weyandt, E.; van Leest, N. P.; de Bruin, B.; Palmans, A. R. A.; Vantomme, G.; Meijer, E. W. (Organic Materials, 2021)
The introduction of a chemical additive to supramolecular polymers holds high potential in the development of new structures and functions. In this regard, various donor- and acceptor-based molecules have been applied in the design of these noncovalent polymers. However, the incorporation of boron–nitrogen frustrated Lewis pairs in such architectures is still rare despite their many intriguing properties in catalysis and materials science. The limited choices of suitable boron derivatives represent one of the main limitations for the advancement in this direction. Here, we examine the use of the commercially available tris(pentafluorophenyl)borane with various triphenylamine derivatives to create supramolecular B–N charge transfer systems. Our results highlight the importance of a proper balance between the donor/acceptor strength and the driving force for supramolecular polymerization to achieve stable, long-range ordered B–N systems. Detailed analyses using electron paramagnetic resonance and optical spectroscopy suggest that tris(pentafluorophenyl)borane displays complex behavior with the amide-based triphenylamine supramolecular polymers and may interact in dimers or larger chiral aggregates, depending on the specific structure of the triphenylamines.
Keywords: supramolecular assembly; tris(pentafluorophenyl)borane; triphenylamine; charge transfer